Atypical Omenn Syndrome due to Adenosine Deaminase Deficiency - Avni Y. Joshi; Erin K. Ham; Neel B. Shah; Xiangyang Dong; Shakila P. Khan; Roshini S. Abraham (Case Reports in Immunology)
We present here a novel case of an atypical Omenn syndrome (OS) phenotype due to mutations in the ADA gene encoding adenosine deaminase. This case is noteworthy for a significant increase in circulating CD56brightCD16- cytokine-producing NK cells after treatment with steroids for skin rash.